Pelican Tracks - Glaser, Elton (Book collections on Project MUSE., 2003)
Pelican Tracks is a book of poems with a homing instinct. Elton Glaser travels a restless circuit between his native Louisiana and his adopted home of Ohio, from the "spice and license of the lowlands" to the "streets of Akron cobbled in ice." These reflections, leavened with a fierce wit and moving bravura of language, are extracted from the origins and ends of the poet's life-his birth in the final spasms of the second World War, the fears and excitements of youth, the death of parents, and the unexpected losses of adulthood. Marking his tracks between the Pelican State a